Can all voices be heard? Active learning strategies enhance FSL oral production - Bello, Sophia (Nouvelle Revue Synergies Canada, 2018)
One of the challenges we face when teaching a language course is how to promote and increase students’ active participation. The instructor does the majority of the talking, and in doing so, neglects to provide enough opportunity for a student’s voice to be heard. This paper considers active learning as the best approach to teaching a second language. The instructor is essentially a learner, not a teacher. In a weekly tutorial section of an advanced FSL course, a group of students must design, present, and deliver a student-run reading workshop. This includes an assigned reading on a specific theme and a PowerPoint presentation. Various activities are used to enhance oral production, three of which are discussed: an online-based activity using Kahoot!, a debate on maternity leave benefits, and team-building through story-telling. Despite a few setbacks, active learning motivates students to take charge and personally contribute to their language learning.